Fragments of a Golden Age : The Politics of Culture in Mexico Since 1940 - Zolov, Eric; Rubenstein, Anne; Joseph, G. M. (Gilbert Michael), 1947- (Book collections on Project MUSE., 2001)
The first cultural history of post-1940s Mexico to relate issues of representation and meaning to questions of power; it includes essays on popular music, unions, TV, tourism, cinema, wrestling, and illustrated magazines.